Eksplorasi Makna dan Nilai dalam Puisi Mantra Bakbrung Hariang Banga - Yessi Hermawati; Yayat Sudaryat; Retty Isnendes; Usep Kuswari; Dede Kosasih (Aksara, 2026)
This study aims to analyze the meaning of the Bakbrung Hariang Banga mantra poem using the pancacuriga approach and to examine its implications for character development in the eight-dimensional graduate profile. Research data were collected through observation, interviews, and documentation of mantra poems from the Cigugurgirang Village community. Data analysis was conducted qualitatively using the pancacuriga semiotic method, which includes five elements of interpretation: silib, sindir, symbol, siloka, and sasmita. The results show that each element of pancacuriga manifests religious, moral, social, and cultural values that are rich in meaning in the mantra poem text. These findings also reveal the connection between the symbolic meaning of mantra poetry and the dimensions of faith, critical reasoning, independence, and communication in the profile of deep learning graduates. The main contribution of this research is the development of the pancacuriga semiotic analysis approach as a comprehensive method in oral literature studies as well as an ethnopedagogical medium for character education based on local wisdom. AbstrakPenelitian ini bertujuan untuk menganalisis makna puisi mantra Bakbrung Hariang Banga menggunakan pendekatan pancacuriga serta mengkaji implikasinya terhadap pengembangan karakter dalam profil lulusan delapan dimensi. Data penelitian dikumpulkan melalui observasi, wawancara, dan dokumentasi teks puisi mantra dari masyarakat Desa Cigugurgirang. Analisis data dilakukan secara kualitatif dengan metode semiotik pancacuriga yang meliputi lima unsur interpretasi: silib, sindir, simbol, siloka, dan sasmita. Hasil penelitian menunjukkan bahwa masing-masing unsur pancacuriga memanifestasikan nilai-nilai religius, moral, sosial, dan kultural yang kaya makna dalam teks puisi mantra. Temuan ini juga mengungkap keterkaitan makna simbolik puisi mantra dengan dimensi keimanan, penalaran kritis, kemandirian, dan komunikasi dalam profil lulusan pembelajaran mendalam. Kontribusi utama penelitian ini adalah pengembangan pendekatan analisis semiotik pancacuriga sebagai metode yang komprehensif dalam kajian sastra lisan sekaligus sebagai media etnopedagogik untuk pendidikan karakter berbasis kearifan lokal.